Ag+ and Cu2+ doped CdS nanorods with tunable band structure and superior photocatalytic activity under sunlight. (October 2017) - Singh, Rohit; Basu, Soumen; Pal, Bonamali
Graphical abstract: A series of Ag + and Cu 2+ doped CdS nanorods are prepared by varying their molar ratios (1 to 10 mol%) and evaluated for photooxidation of salicylaldehyde and photoreduction of m -dinitrobenzene under sunlight irradiation. The efficiency of CdS nanorods markedly improved with gradual doping, which is well explained in terms of tuning band edge potentials, crystal distortion, and homogeneous dispersion of charge carriers. Abstract: The influence of Ag + and Cu 2+ doping (1 to 10 mol%) on the optical, structural and photocatalytic properties of CdS-nanorods is systematically studied. Doping of metal ions slightly distorts the hexagonal-phase of CdS though they have a strong bonding interaction with S 2− . The bandedge positions of CdS-nanorods are significantly shifted; 2.56 → 2.29 eV and 2.56 → 2.31 eV with gradual doping of Ag + and Cu 2+ ions. The catalytic-activity is studied by photooxidation of salicyladehyde and photoreduction of m -dinitrobenzene under sunlight. The activity is improved with doping, where Ag x Cd1- x S ( x = 0.1) composite displayed the highest photooxidation of 0.5 mM salicylaldehyde ( > 90%) and photoreduction of 5 mM, m -DNB (89.6%) to m -NA (38%) and m -PDA (52%) as compared to pure CdS and Cu x Cd1− x S ( x = 0.1) composite. It is found that doping in CdS results in narrowing of bandedge potentials and distortion in the crystal that leads to weakening of bonds to avail charge carriers for corresponding reactions.